THE FAMILY FINANCIAL LITERACY TRAINING FOR HEALTHY AND RESPONSIBLE DEBT MANAGEMENT - Yusuf, Maulana Ghani; Oktabriyantina, Wulan; Sanjoko, Deny Cahyadinanto; Khusniati, Navi’ah (EZRA SCIENCE BULLETIN, 2025)
Debt management is an important thing, especially in a family. If debt is not managed properly, it can pose risks both financially and socially for the family. The purpose of this study was to evaluate the effectiveness of family financial literacy training so that family debt management becomes healthier and more responsible. The research method is a quasi-experimental approach and a pretest-posttest tool conducted on PKK RT3 mothers training participants in Griya Beringin Asri Housing. The training materials include how to manage income, calculate debt ratio limits, and strategies for debt repayment. The results of this study are that there is a significant increase in training participants regarding debt risk, payment priority scales, and considerations in making wiser family financial management decisions. Based on these findings, it can be seen that community service activities with the theme of financial literacy training based on debt management can be used as a fairly effective intervention in improving family financial health.